Female Labor Force Participation in Sub-Saharan Africa: A Cohort Analysis - Andreas Backhaus; Elke Loichinger (Population and Development Review, 2022)
Female labor force participation rates have been stagnating despite rising female education in sub-Saharan Africa since the turn of the millennium. Using representative and repeated census data from a heterogeneous sample of 13 sub-Saharan African countries, this paper analyzes female labor force participation from a demographic perspective. We show that enrollment in education is substantially higher among the most recent female cohorts than among the earlier-born ones. The higher enrollment mechanically depresses female labor force participation, weakening the relationship between female labor force participation and education. After taking this cohort trend into account, we find a strong and positive association between female labor force participation and female education. We further find a cohort trend toward higher female employment in the nonprimary sector and a positive association between female employment in the nonprimary sector and female education. The higher investments in education by younger female cohorts, together with the demographics of sub-Saharan African countries, have implications for a potentially arising “demographic dividend”.
Keywords: 300